The Patient and Carer Race Equality Framework: a model to reduce mental health inequity in England and Wales - Smith, Shubulade Mary; Kheri, Amna; Ariyo, Kevin; Gilbert, Steve; Salla, Anthony; Lingiah, Tony; Taylor, Clare; Edge, Dawn (Frontiers in Psychiatry, 2023)
The Patient and Carer Race Equality Framework (PCREF) is an Organisational Competence Framework (OCF), recommended by the Independent Review of the Mental Health Act as a means to improve mental health access, experience and outcomes for people from ethnic minority backgrounds, particularly Black people. This is a practical framework that should be co-produced with and tailored to the needs of service users, based on quality improvement and place-based approaches. We aim to use the PCREF to address the longstanding epistemic justices experienced by people with mental health problems, particularly those from minoritised ethnic groups. We will outline the work that led to the proposal, the research on racial inequalities in mental health in the UK, and how the PCREF will build on previous interventions to address these. By taking these into account, the PCREF should support a high minimum standard of mental health care for all.